2021
DOI: 10.1111/imcb.12490
|View full text |Cite
|
Sign up to set email alerts
|

A preliminary investigation into the immune cell landscape of schistosome‐associated liver fibrosis in humans

Abstract: Schistosomiasis is a widespread helminth disease that poses a heavy social and economic burden on people worldwide. Advanced schistosomiasis often develops into schistosome-associated liver fibrosis, the pathogenesis of which remains unclear. This study aimed preliminarily to profile immune cells of schistosome-associated liver fibrosis using single-cell RNA sequencing. Three patient groups were enrolled, including an Schistosomiasis japonicum (SJ) group (n = 1), a chronic liver failure (CLF) group (n = 3) and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 35 publications
0
5
0
Order By: Relevance
“…Our results showed that CXCR2 + NKT cells might migrate to the liver via chemotaxis and exhibit both cytotoxic and proinflammatory activity. Our previous study also showed that GZMB + T cells are increased in schistosome -associated liver fibrosis [ 37 ]. Previous studies have also demonstrated the importance of NKT cells in hepatic inflammation and fibrosis.…”
Section: Discussionmentioning
confidence: 93%
“…Our results showed that CXCR2 + NKT cells might migrate to the liver via chemotaxis and exhibit both cytotoxic and proinflammatory activity. Our previous study also showed that GZMB + T cells are increased in schistosome -associated liver fibrosis [ 37 ]. Previous studies have also demonstrated the importance of NKT cells in hepatic inflammation and fibrosis.…”
Section: Discussionmentioning
confidence: 93%
“…Cell population source analysis and immunofluorescence labeling showed that the mouse fibrosis model contained highly expressing Ccr2 and Cd68 cell populations (Figures 4E, H , and S3B ). Cells in cluster 2 were identified as Kupffer cells (KCs) because of the high expression of KC marker genes Clec4f , Macro and Timd4 42 (Figures 4F and G ). Percent cell population analysis and Clec4f immunofluorescence staining indicated that this cell population was mainly derived from normal mouse liver (Figures 4E and I ).…”
Section: Resultsmentioning
confidence: 99%
“…Advanced schistosomiasis often progresses to liver fibrosis and cirrhosis. To characterise the transcriptomic atlas of liver immune cells involved in schistosoma-associated fibrosis, scRNA-seq analysis was performed on liver samples from fibrotic patients coinfected with S. japonicum (SJ) schistosoma and HBV, patients with HBV cirrhosis, and healthy controls [ 153 ]. Despite the small sample size, this study revealed that T cells, particularly granzyme B (GZMB)+ T cells, were a major subgroup of liver-resident immune cells and increased in the SJ group.…”
Section: Spatial and Single-cell Transcriptomics In The Liver During ...mentioning
confidence: 99%